Improving Students' Comprehension of Announcement Text Through Wayground in Communicative Language Teaching (Lembaga Pengembangan Kinerja Dosen, 2026)
The purpose of this study was to investigate whether students’ reading comprehension could be improved the use of Wayground as a learning medium. This research applied a pretest–posttest control group design involving two classes of 12th-grade students. The control class consisted of 31 students (9 male and 22 female) who were taught using conventional methods without Wayground. Meanwhile, the experimental class consisted of 32 students (10 male and 22 female) who were taught using Wayground with an announcement text reader. To measure reading comprehension, all students were given a 40-point multiple-choice test. The assessment focused on five reading components: identifying main ideas, understanding specific information, inferring vocabulary in context, recognizing text structures, and drawing conclusions. The analysis revealed a significant improvement in the experimental class after the use of Wayground. The average score increased from the pre-test to the post-test, showing a notable gain. Students demonstrated better ability in identifying key ideas, finding detailed information, inferring meaning, understanding vocabulary, and determining the purpose of texts. Overall, the findings indicate that Wayground had a positive effect on students’ reading comprehension. The results suggest that integrating digital tools into communicative language teaching can enhance engagement, motivation, and reading achievement.